Computer Safety, Reliability, and Security : SAFECOMP 2015 Workshops, ASSURE, DECSoS. ISSE, ReSA4CI, and SASSUR, Delft, The Netherlands, September 22, 2015, Proceedings - Koornneef, Floor; van Gulijk, Coen.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book constitutes the refereed proceedings of 5 workshops co-located with SAFECOMP 2015, the 34th International Conference on Computer Safety, Reliability, and Security, held in Delft, The Netherlands, in September 2015. The 36 revised full papers presented were carefully reviewed and selected from numerous submissions. This year s workshop are: ASSURE 2015 - Assurance Cases for Software-intensive Systems; DECSoS'15 - EWICS/ERCIM/ARTEMIS Dependable Cyber-physical Systems and Systems-of-Systems Workshop; ISSE'15 - International workshop on the Integration of Safety and Security Engineering; ReSA4CI 2015 - International Workshop on Reliability and Security Aspects for Critical Infrastructure Protection; SASSUR 2015 - International Workshop on Next Generation of System Assurance Approaches for Safety-Critical Systems. .
Keywords: Logic design; Software engineering; Computer security; Computer network architectures; Logics and Meanings of Programs; Software Engineering; Systems and Data Security; Computer Systems Organization and Communication Networks